Decoding enigma: Turner syndrome with ring chromosome. Issue 11 (28th December 2021) - Das, Debarup; Roy, Debaditya; Basu, Kaushik; Sarkar, Anupam
ABSTRACT: Ring chromosome X is one of the rarest with some unique phenotypical features in Turner syndrome. A young female presented to us with anasarca developed over the past 2 months due to congestive cardiac failure along with jaundice and orthopnea. She had growth retardation, intellectual disability, primary amenorrhea, lack of secondary sexual character development and dysmorphic features like low posterior hairline, shield chest and cubitus valgus. She had dilated cardiomyopathy (DCM) with intracardiac thrombus on echocardiography. Skeletal survey revealed short fourth metacarpal/tarsal on limbs. Karyotyping showed a mosaic pattern, with 45, X/46, X, r(X)(p22.3q28), i.e. Turner syndrome karyotype with ring chromosome. Her heart failure with reduced ejection fraction was managed with vasopressor along with anticoagulant and given oral contraceptive pills for hormone replacement therapy. The ring chromosomal pattern of karyotype in this patient and DCM is a rare cardiological phenomenon that can be associated with Turner syndrome, making this case a unique one.